2018
DOI: 10.1016/j.drugalcdep.2017.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use among US tobacco users: Findings from wave 1 of the population assessment of tobacco health (PATH) study

Abstract: A B S T R A C TBackground: With an increase in marijuana use among adults in the United States (US), understanding the potential impact of marijuana use on tobacco use and associated behavioral and health consequences, including respiratory conditions, is necessary. Method: Survey responses from Wave 1 of the nationally representative Population Assessment of Tobacco and Health (PATH) Study were used to assess tobacco use and marijuana use among non-current tobacco users (n = 17,952) and current established to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 43 publications
(45 reference statements)
7
42
0
Order By: Relevance
“…Further, youth classi ed as E-cigarette Users or Polytobacco Users had over 20-fold increased odds of being current marijuana users compared to Non-Users. The present study con rms prior ndings of the signi cant association of marijuana use with tobacco use (14,16) and highlights the need for prevention scientists to consider comorbid intervention designs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further, youth classi ed as E-cigarette Users or Polytobacco Users had over 20-fold increased odds of being current marijuana users compared to Non-Users. The present study con rms prior ndings of the signi cant association of marijuana use with tobacco use (14,16) and highlights the need for prevention scientists to consider comorbid intervention designs.…”
Section: Discussionsupporting
confidence: 83%
“…Epidemiological studies have consistently found an association between tobacco and marijuana use in youth and young adults (14,15); however, Black youth are more likely to report co-use (14,16,17). Co-use of tobacco and marijuana is of particular interest given the documented disparities in tobacco-related health outcomes (1,11) as well as in health and social outcomes of marijuana use (18) experienced by U.S.…”
Section: Co-use Of Marijuana and Tobacco And Black Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the study was cross-sectional and temporal relations between variables cannot be definitively established. Second, the study lacked a detailed measure of smoking history and the survey did not include items on marijuana, which is relevant for asthma (Strongetal., 2018). Though prior studies have shown effects for e-cigarettes independent of marijuana (e.g., Schweitzer et al, 2017), this is a possible limitation and needs to be extended in further research.…”
Section: Discussionmentioning
confidence: 99%
“…5 Adults who use cannabis are more likely to report cigarette use, 4,6 and conversely, cigarette smokers are more likely to report cannabis use. 5,7 Despite the increasing use of cannabis, changes in cannabisrelated legislation in the United States and other countries, and the relationship between cannabis and cigarettes, it is unclear whether and how cannabis use may be associated with cigarette use among current, former, and lifetime nonsmoking adults in the United States. There is evidence for a "reverse gateway effect" where cannabis use leads to cigarette use among adolescents.…”
Section: Introductionmentioning
confidence: 99%